A Comparative Study of Design Strategies for Lobby of Outpatient Department of Hospital Buildings in Cold Climate Region in China. (2017) - Sun, Yizhao; Huang, Qiong
Abstract: This paper aims to clarify the relationship among lobby-design, energy consumption and daylight environment of outpatient department in hospital buildings, and further goal is to explore effective design strategies for outpatient lobby in hospitals for better healthcare environment while lower energy consumption. Firstly, investigation that focused on thermal and daylighting environment on current hospitals was carried out in Tianjin. Based on the investigational data, it is concluded that space-design and façade-design are both the main factors that impact physical environment. Then simulation was conducted to study how these factors affect energy consumption and physical environment. In the first study that concerns the space-design of lobby, four basic comparative models with different positions of lobby were built up to compare energy consumption and daylighting environment; then for further analysis, space orientation and height were studied. The results of simulations in the first study indicates that: (1) Concerning the position, Form I case has the lowest energy consumption level and the most satisfactory interior daylight environment; (2) Concerning the orientation, w-orientated case has the highest energy consumption level while s-orientated case has the lowest level; (3) Concerning the height, it shows that increase of lobby's height brings great increase in energy consumption while no obvious help in improving daylighting environment. In the second study that concerns façade-design of lobby, both window-wall ratio and skylight ratio were analyzed. The results of simulations in the second study show that: (1) Concerning window-wall ratio, the raise of the ratio has insignificant impact on increasing energy consumption level but noticeable impact on developing the interior daylight environment; (2) Concerning skylight ratio, the raise of the ratio causes great increase in both energy consumption level and daylight availability, which might lead to excessive consumption and daylight availability under extreme condition.